Online Dictionary and Manual Dictionary: Which One Is Used More? - Aula Akramah; Audria Bella Alifva; Dewi Yani; Mastura Mastura; Zahratul Idami (English LAnguage Study and TEaching, 2020)
This study aimed to find out the use of the manual dictionary and electronic dictionary in learning and daily activity by the students in the University of Serambi Mekkah, Banda Aceh. This study used descriptive qualitative method for the data collection. The population in this study were the students at the University of Serambi Mekkah and the sample used in this study was 30 English major students in the University of Serambi Mekkah. The researcher used a questionnaire and interview in collecting the data. In analyzing the data, the researcher used percentage formula. The result of the study showed that 63% of students often used the manual dictionary, 96% of students often used the electronic dictionary. Meanwhile, the students majoring at English department in the University of Serambi Mekkah commented about the benefit of using the dictionary was that it could help adding the vocabulary and made the learning process easier.